Excess Serum Interleukin‐18 Distinguishes Patients With Pathogenic Mutations in PSTPIP1. Issue 2 (3rd January 2022) - Stone, Deborah L.; Ombrello, Amanda; Arostegui, Juan I.; Schneider, Corinne; Dang, Vinh; de Jesus, Adriana; Girard‐Guyonvarc'h, Charlotte; Gabay, Cem; Lee, Wonyong; Chae, Jae Jin; Aksentijevich, Ivona; Goldbach‐Mansky, Raphaela T.; et al.
Abstract : Objective: Dominantly inherited PSTPIP1 mutations cause a spectrum of autoinflammatory manifestations epitomized by PAPA syndrome (pyogenic sterile arthritis, pyoderma gangrenosum, and acne (PAPA) syndrome.). The connections between PSTPIP1 and PAPA syndrome are poorly understood, although evidence suggests involvement of pyrin inflammasome activation. Interleukin‐18 (IL‐18) is an inflammasome‐activated cytokine associated with susceptibility to macrophage activation syndrome (MAS). This study was undertaken to investigate an association of IL‐18 with PAPA syndrome. Methods: Clinical and genetic data and serum samples were obtained from patients referred to institutions due to symptoms indicative of PAPA syndrome. Serum IL‐18, IL‐18 binding protein (IL‐18BP), and CXCL9 levels were assessed by bead‐based assay, and free IL‐18 levels were assessed by enzyme‐linked immunosorbent assay. Results: The symptoms of PSTPIP1 ‐positive patients with PAPA syndrome overlapped with those of mutation‐negative patients with PAPA‐like conditions, but mutation‐positive patients had earlier onset and a greater proportion had a history of arthritis. We found uniform elevation of total serum IL‐18 in treated PAPA syndrome patients at levels nearly as high as those seen in NLRC4‐associated autoinflammation with infantile enterocolitis patients, and well above levels found in most familial Mediterranean fever patients. Serum IL‐18 elevation in PAPA syndrome patients persisted despite fluctuations in disease activity. Levels of the soluble IL‐18 antagonist IL‐18BP were modestly elevated, and PAPA syndrome patients had detectable free IL‐18. PAPA syndrome was rarely associated with elevation of CXCL9, an indicator of interferon‐γ activity, but no PAPA syndrome patients had a history of MAS. Conclusion: PAPA syndrome is a refractory and often disabling monogenic autoinflammatory disease associated with chronic and unopposed elevation of serum IL‐18 levels but not with risk of MAS. These findings affect our understanding of the diseases in which IL‐18 is overproduced and suggest a link between pyrin inflammasome activation, IL‐18, and autoinflammation, without susceptibility to MAS.